Modality vs. Chordal Harmony : Hybrid Aspects of Rebetiko During the Interwar Period - Delegos, Spiros (Hellenic Musicological Society, 2021)
This paper addresses the contribution of modality, chordal harmony and the relationship between them to the formulation of ‘Rebetiko’ –a musical genre of Greek Urban Popular Music– during the interwar period. The aim of the research is to show the hybrid character of Rebetiko through the analysis of the confrontation between the makam modality and an idiosyncratic form of chordal harmony, transcending the typical East-West dipole. After having listened to a large corpus of gramophone recordings of that period, I chose some of the most representative musical pieces –in terms of harmonization and modality– in order, firstly, to document them in transcriptions and, secondly, to analyze and interpret them within their socio-cultural context. The establishment of the equal tempered three-course bouzouki and the censorship by Metaxas’ regime are peculiar forms of modernization and westernization respectively, which contributed to the hybrid aspects of this genre. The interplay between the Greek and the other ethnic communities within the eastern Mediterranean context, the deterritorialization of the musical culture from the broader area of Anatolia to the Greek state due to the Greek refugee movement (1922-23) are some of the basic factors which facilitate the understanding of the cultural osmosis responsible for this musical syncretism.
Keywords: musiikki; Kreikka; populaarimusiikki; musiikinhistoria; historia; taidemusiikki; soinnutus; maailmansotien välinen aika; musiikinteoria; musiikintutkimus